Research on Iterative Calibration Method of Linear Model Parameters of Gravity Sensor. Issue 4 (April 2020) - Lu, Shuhai; Cao, Juliang; Shaokun, Cai; Yu, Ruihang; Yang, Bainan
Abstract: In recent years, the calibration method of Strapdown gravimeter has become the bottleneck of relative gravity measurement accuracy. Based on this situation, this thesis studies the parameter iterative calibration method of SGA-WZ03 strapdown gravimeter to break the bottleneck of relative gravity measurement and further improve the measurement accuracy of relative gravimeter in flight experiment through the improvement of calibration method Degree. The parameter iterative estimation algorithm is based on the pulse output model of a single accelerometer to establish the linear pulse output model of the accelerometer components. Using the idea of parameter separation, the two-step iterative estimation of the model parameters and the tilt vector can complete the calibration of the linear model and the secondary model of the accelerometer. Compared with the traditional 24 bit calibration method, the parameter estimation iterative estimation calibration method has better stability than the traditional method.